Periodic orbits around 216-Kleopatra asteroid modelled by a dipole-segment - Abad, Alberto; Elipe, Antonio; Ferreira, Alessandra F.S. [UNESP] (Elsevier, 2024)
Asteroid 216-Kleopatra presents a ham-bone shape, that is to say, it is quite elongated body with two protuberances on its end-points, which makes of it the perfect candidate to model its shape and mass distribution by a Dipole-Segment, consisting on a massive segment with two spherical masses at the end-points of the rod and that is rotating about its center of mass with uniform velocity. Once obtained an approximation of the actual values of the involved parameters from recent results of Burov and coworkers, we obtain the complete map of families of symmetric periodic orbits, and describe the orbits of the different families, its parametric evolution, stability and also we compute the heteroclinic orbits connecting unstable isosceles equilibria.
Keywords: Asteroid gravitational potential; Dipole-Segment gravitational field; Families of periodic orbits; Orbital dynamics